OP V – 6 A study of school-going children on neurobehavior and currently used agricultural pesticide exposure in the rural western cape, south africa. (18th March 2018) - Shala, Chetty-Mhlanga; Basera, Wisdom; Dalvie, Aqiel; Roosli, Martin; Fuhriman, Samuel; Probst-Hensch, Nicole
Abstract : Background/aim: There is limited and conflicting epidemiological evidence on the long-term health effects of currently used agricultural pesticides in children. We aim to investigate neurobehavioral effects due to pesticide exposure in school children in the rural Western Cape (WC), one of the largest fruit producing agricultural areas in South Africa. Methods: The 3 year cohort study entails a baseline (2017), 4 monthly exposure assessments covering all seasons in the second year and a final follow-up (2019) examination of 1.000 children aged 9–16 years old, from three different agricultural farming areas in the WC region. Exposure to neurotoxic pesticides is measured in urine and hair samples and questionnaires related to pesticide contact including confounding variables. Further, pesticides measured in air and water samples will describe environmental occurrence over the study period. The primary outcome of cognitive functioning is measured through the iPad-based Cambridge Neuropsychological Test Automated Battery (CANTAB) including dimensions for attention, memory, executive functioning, and processing speed. Results: Between April and September we enrolled 950 children in the baseline survey, including 53% females and 47% males, 9 to 16 years (11±1.69) in grade 1 to 8 (4±1.6) distributed equally over the three farm areas ( 30%). Almost half of the children (47%) have parents who are farmworkers and live on a farm (45%). Majority of participants (96%) coresponded accurately on all 10 preliminary assessment trials to continue further cognitive testing. As an example, the reaction time in the motor screening test ranged from 475 to 3730 milliseconds, median time 875 ms (25th percentile=703 ms; 75th percentile=1266 ms). The response latency during the average correct responses when measuring sustained attention, ranged from 179 to 1739 ms, median time 443 ms (25th percentile=361 ms; 75th percentile=531 ms) Conclusion: Preliminary data suggest adequate data distribution for farm and non-farm exposure, to investigate effects. We present for the first time a study using the CANTAB test battery and pesticide exposure in South Africa. Further analysis will determine potential associations between the exposure and neurobehavior of children by controlling for a wider range of confounders from a guardian survey